2021
DOI: 10.1007/s11571-021-09701-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term predictions of current confirmed and dead cases of COVID-19 in China by the non-autonomous delayed epidemic models

Abstract: In this paper, we make long-term predictions based on numbers of current confirmed cases, accumulative dead cases of COVID-19 in different regions in China by modeling approach. Firstly, we use the SIRD epidemic model (S-Susceptible, I-Infected, R-Recovered, D-Dead) which is a non-autonomous dynamic system with incubation time delay to study the evolution of the COVID-19 in Wuhan City, Hubei Province and China Mainland. According to the data in the early stage issued by the National Health Commission of China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…Regression outcomes provided coarse estimates of controlling performance comparisons of COVID-19 pandemic. This study was in line with early simulation outcomes which found that their NH rates were the approximately linear increasing functions and the ND rates were the small constants [ 42 ]. This could partially explained by an early study which indicated that socio-economic determinants and city sizes had high impacts on the change of COVID-19 transmission in China [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Regression outcomes provided coarse estimates of controlling performance comparisons of COVID-19 pandemic. This study was in line with early simulation outcomes which found that their NH rates were the approximately linear increasing functions and the ND rates were the small constants [ 42 ]. This could partially explained by an early study which indicated that socio-economic determinants and city sizes had high impacts on the change of COVID-19 transmission in China [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…The removed rate is approximately a piecewise linear increasing function instead of a linear increasing function which is ( + b )heaviside( t -14). They are very different from those of the previous SIR model [ 18 , 19 ] and bring about the more accurate predictions of the COVID-19 epidemics. Due to the degree of illness and personal recovery, the first recovery may appear at different times, which it is roughly on the 14th day.…”
Section: Introductioncontrasting
confidence: 69%
“…Alos [ 14 ], Lounis [ 15 ], Ferrari [ 16 ], and Sedaghat [ 17 ] used SIRD model to predict the spread trend of COVID-19 in some countries. Long-term forecast of COVID-19 was made in some regions at home and abroad in [ 18 , 19 ]. The PSO algorithm was used for parameter estimation of SEIR model by He [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many countries are already experiencing economic downturns due to the COVID-19 pandemic. Many scholars made use of the existing data to model and predict the development trend of the epidemic [5][6][7] and gave some suggestions on epidemic control from the perspective of mathematics. Xiao et al analyzed the piecewise incidence rate in a SIR system to show the effect of threshold densities and control intensities on the outbreak of infectious disease [8].…”
Section: Introductionmentioning
confidence: 99%